Analisis Risiko Ergonomi Pada Petani Karet Di Desa Beringin Jaya Way Tuba Kabupaten Way Kanan, Lampung - Wibawa, Muhammad Gede; ZulArdi, Subhan (Universitas Ahmad Dahlan, 2022)
Background: Some methods for evaluating work postures include RULA, REBA, OWAS and QEC. Beringin Jaya Village there are 387 families with a population of 1,255 people. 85% of the population work as rubber farmers. Some rubber farmers in Beringin Jaya Village, farmers experience complaints of pain in the neck and back. The purpose of this study is to analyze the ergonomic risk of rubber farmers in the Beringin Jaya Village, Way Tuba, Way Kanan Regency, Lampung Methods: The design of this study was descriptive qualitative with a case study design and using the REBA survey tool. The research subjects in this study were rubber farmers in Beringin Jaya Village, Way Tuba, Way Kanan Regency, Lampung. The sampling technique in this study is snow ball sampling technique. The type of data in this study is primary data, obtained through observation, measurement and interviews. data analysis with Miles and Huberman modes. Results: the level of ergonomics risk in the treatment process scores 11+, the harvesting process scores 11+ at the tapping stage, the rubber gum scavenging stage scores 11+, the sales process gets a final score of 9. Conclusion: the level of ergonomic risk in all the work processes of farmers in Beringin Jaya Village, Way Tuba, Way Kanan district, Lampung Province get high to very high risk levels.